2008
DOI: 10.1102/1470-7330.2008.0018
|View full text |Cite
|
Sign up to set email alerts
|

MRI of pulmonary nodules: technique and diagnostic value

Abstract: Chest wall invasion by a tumour and mediastinal masses are known to benefit from the superior soft tissue contrast of magnetic resonance imaging (MRI). However, helical computed tomography (CT) (i.e. with multiple row detector systems) remains the modality of choice to detect and follow lesions of the lung parenchyma. Since minimizing radiation exposure plays a minor role in oncologic patients, there are only few routine indications for which MRI of lung parenchyma is preferred to CT. This includes whole body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
42
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 10 publications
2
42
0
1
Order By: Relevance
“…With the introduction of fully integrated PET/MRI systems, PET and MRI can be used synergistically in a single modality, taking advantage of an exact correlation between 18 F-FDG-avid lesions and the anatomic details obtained by MR images (10)(11)(12)). Yet, regarding lung imaging, even when using high spatial resolution T1-weighted (T1w) 3-dimensional (3D) gradient echo (GRE) sequences (e.g., volume-interpolated breathholdexamination [VIBE]) recommended for the identification of small pulmonary nodules (13)(14)(15), PET/MRI seems to be outmatched by PET/CT (16). Underlying reasons are found in PET/MRI's lower sensitivity regarding 18 F-FDG-negative lesions (17,18) because of a low proton density in aerated lungs, fast decay of signal caused by susceptibility artifacts at air-tissue boundaries, and motion artifacts caused by breathing and cardiac pulsation.…”
mentioning
confidence: 99%
“…With the introduction of fully integrated PET/MRI systems, PET and MRI can be used synergistically in a single modality, taking advantage of an exact correlation between 18 F-FDG-avid lesions and the anatomic details obtained by MR images (10)(11)(12)). Yet, regarding lung imaging, even when using high spatial resolution T1-weighted (T1w) 3-dimensional (3D) gradient echo (GRE) sequences (e.g., volume-interpolated breathholdexamination [VIBE]) recommended for the identification of small pulmonary nodules (13)(14)(15), PET/MRI seems to be outmatched by PET/CT (16). Underlying reasons are found in PET/MRI's lower sensitivity regarding 18 F-FDG-negative lesions (17,18) because of a low proton density in aerated lungs, fast decay of signal caused by susceptibility artifacts at air-tissue boundaries, and motion artifacts caused by breathing and cardiac pulsation.…”
mentioning
confidence: 99%
“…(2,3) It is now possible to perform magnetic resonance angiography (MRA) of the pulmonary arteries with high spatial resolution, for the diagnosis of suspected pulmonary embolism or pulmonary hypertension, as well as multiphase MRA with high temporal resolution, for the depiction of vascular territories and of pulmonary perfusion (4) Most lung diseases are accompanied by an increase in the quantity of tissue, cells, or blood within the lungs, which facilitates MRI because it makes more protons available to generate a signal. (5)(6)(7)(8) Therefore, structural MRI is feasible, and tissue can be characterized by the differences observed among T1-weighted, T2-weighted, and other types of sequences, as well as by the assessment of contrast-enhanced images. In the staging of lung cancer, MRI has proven to be superior to CT, and there is evidence that it is also superior in the characterization of pulmonary nodules larger than 1 cm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…In the staging of lung cancer, MRI has proven to be superior to CT, and there is evidence that it is also superior in the characterization of pulmonary nodules larger than 1 cm in diameter. (6)(7)(8) In addition, MRI has advantages in the characterization of pulmonary infiltrates, Magnetic resonance of the lung: a step forward in the study of lung disease* , every year. (9) One recent meta-analysis reported that dynamic CT and MRI, both of which are noninvasive methods, are equally accurate in distinguishing between malignant and benign solitary pulmonary nodules, the differences between the two tests being insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has played only a minor role in radiologic assessment of the lung, mainly because of methodologic and physical shortcomings such as low proton density in aerated lungs, fast decay of signal, and motion artifacts caused by breathing and cardiac pulsation. When different MRI sequences are compared, it is the T1-weighted 3-dimensional (3D) gradient echo sequences-such as T1-weighted volume-interpolated breath-hold examination (VIBE)-that demonstrate the highest sensitivity and thus are recommended for MR-based identification of pulmonary lesions (3)(4)(5). Nevertheless, several studies have indicated that lesion detection on MRI remains inferior to that on CT (4,10,11).…”
mentioning
confidence: 99%
“…CT, offering high spatial resolution of pulmonary tissue, has been regarded as the reference standard for lung lesion detection (4,5). However, because morphologic CT-based criteria have a relatively low specificity for malignant versus benign character, there has been a need for a more robust diagnostic standard.…”
mentioning
confidence: 99%